2014
DOI: 10.1371/journal.pone.0098005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Endo-Ovarian Tissue Biopsy and Pelvic Aspirated Fluid for the Diagnosis of Female Genital Tuberculosis by Conventional versus Molecular Methods

Abstract: BackgroundTil date, none of the diagnostic techniques available for the detection of female genital tuberculosis (FGTB) are 100% accurate. We therefore, proposed to use the endometrial tissue biopsies (ETBs), ovarian tissue biopsies (OTBs) and pelvic aspirated fluids (PAFs) for the diagnosis of FGTB among infertile women by conventional versus molecular methods.Methodology/Principal FindingsA total of 302 specimens were collected both from 202 infertile women highly suspected of having FGTB on laparoscopy exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 49 publications
1
43
1
Order By: Relevance
“…However, PCR is associated with high false positive rates and therefore it is not recommended to start the treatment for FGTB on the basis of PCR results only. 14,15 The use of geneXpert has been advocated by world health organization for the detection of Mycobacterium tuberculosis and rifampicin susceptibility. Gene Xpert was done in 69 patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, PCR is associated with high false positive rates and therefore it is not recommended to start the treatment for FGTB on the basis of PCR results only. 14,15 The use of geneXpert has been advocated by world health organization for the detection of Mycobacterium tuberculosis and rifampicin susceptibility. Gene Xpert was done in 69 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutional symptoms such as sweating, evening rise of temperature and weight loss were not major complaints, while local organ dysfunction manifested in amenorrhoea, omental adhesions and bilateral tubal blockage are seen on hysterosalpingographic studies. All samples collected were examined by haematoxylin and eosin (H & E) staining [ 83 ], Z–N staining for acid fast bacilli (AFB) [ 84 ], as well as culture on Löwenstein—Jensen (L–J) egg media [ 85 ] and the MTB-specific multi-gene/multi-primer polymerase chain reaction (PCR) method [ 86 ] by which FGTB was confirmed. MTB [American type of culture collection (ATCC) 35836] reference stain isolates provided by the Department of Microbiology, Nizam’s Institute of Medical Sciences (NIMS), Hyderabad, India, were used as controls in each assay.…”
Section: Methodsmentioning
confidence: 99%
“…PCR: PCR tests targeting IS6110, hsp65 (Rv0440), mpt64, fbp, mtp40 (Rv2351c), TRC4 (conserved repetitive element) -among others, have been devised using endometrial aspirates, EBs, renal biopsies, menstrual blood and urine specimens [2,4,10] but they often lead to false-positive and false-negative results. Detection of male UGTB within semen samples by PCR has also been reported that revealed superiority over MGIT-960 culture [6].…”
Section: Naatsmentioning
confidence: 99%
“…M-PCR/real-time PCR: To improve the sensitivity of PCR, Bhanothu et al [10] designed M-PCR using mpt64+LpqH (Rv3763)+TRC4+mpt59-α (fbp) within EBs, ovarian biopsies and pelvic aspirates of suspected female UGTB cases. Compared with smear/culture and histopathology, M-PCR showed an improvement for the detection of UGTB cases.…”
Section: Naatsmentioning
confidence: 99%